KEBERHASILAN PEMBERDAYAAN EKONOMI MASYARAKAT DALAM EKSPOR KERAJINAN SANGKAR BURUNG - Sulikah Asmorowati; Dyah Kuntorini Dwi Angreni (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2021)
Bird cage craft is a economy creative effort that utilizes local potential as well as hone abilities and skills. Bird cage made of wood with added carvings. The management of bird cage crafts is able to improve the economy of the residents of Gedog Wetan Village, Turen District, Malang Regency. Able to produce super quality with marketing outside Java and even export to Mexico. The research approach carried out by the researcher is a type of qualitative research. The research objective is to describe the empowerment of the community in managing bird cage crafts and the impact on improving the economy of the community of Gedog Wetan Village. The economic empowerment of village communities in making bird cages has good future prospects so that it can become a characteristic of the village and be able to prosper the economy of the village community. The proposed model was approved and has been applied to next year's government budget as a pilot project with the support of various stakeholders. It is hoped that this model will be able to accelerate rural economic development and the expansion of handicraft businesses that are managed in a sustainable manner.